Pengaruh kompensasi, motivasi dan lingkungan kerja, terhadap kinerja karyawan melalui kepuasan kerja karyawan sebagai variabel intervening di PLTGU Proyek Muara Tawar - Marcelia, Elizabeth; Efendi, Suryono; Sugiono, Edi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The business world is now required to create high employee performance for company development. Companies must be able to build and improve performance in their environment. The success of the company is influenced by several factors, one of the important factors is human resources, because human resources are actors from all levels of planning to evaluation who are able to utilize other resources owned by the organization or company. The purpose of this study was to determine the effect of knowledge of compensation, motivation and work environment on employee performance and job satisfaction at the Muara Tawar PLTGU Project. This study uses quantitative analysis methods. Data were collected as many as 174 respondents using probability sampling method and processed with IBM AMOS v24 and SPSS software. The results of this study indicate that the effect of compensation, motivation and work environment has a significant effect on job satisfaction and employee performance